Introgression of Blast Resistance Genes (Putative Pi-b and Pi-kh) into Elite Rice Cultivar MR219 through Marker-Assisted Selection - Tanweer, Fatah A.; Rafii, Mohd Y.; Sijam, Kamaruzaman; Rahim, Harun A.; Ahmed, Fahim; Ashkani, Sadegh; Latif, Mohammad A. (Frontiers in Plant Science, 2015)
Blast is the most common biotic stress leading to the reduction of rice yield in many rice-growing areas of the world, including Malaysia. Improvement of blast resistance of rice varieties cultivated in blast endemic areas is one of the most important objectives of rice breeding programs. In this study, the marker-assisted backcross breeding (MABB) strategy was applied to improve the blast resistance of the most popular Malaysian rice variety MR219 by introgressing blast resistance genes from the Pongsu Seribu 2 variety. Two blast resistance genes, Pi-b and Pi-kh, were pyramided into MR219. Foreground selection coupled with stringent phenotypic selection identified 15 plants homozygous for the Pi-b and Pi-kh genes, and background selection revealed more than 95% genome recovery of MR219 in advanced blast resistant lines. Phenotypic screening against blast disease indicated that advanced homozygous blast resistant lines were strongly resistant against pathotype P7.2 in the blast disease endemic areas. The morphological, yield, grain quality and yield-contributing characteristics were significantly similar to those of MR219. The newly developed blast resistant improved lines will retain the high adoptability of MR219 by farmers. The present results will also play an important role in sustaining the rice production of Malaysia.